Manajemen Promosi Melalui Media Sosial Instagram Dapat Menambah Minat Berkunjung Ke The Lawu Park - Aries Dwi Laksono; Darmaesti Darmaesti; Bartolomeus Herawan Mintarjo (JURNAL ILMIAH EDUNOMIKA, 2024)
In this digital era, Instagram is a social network that is quite popular in various circles. Instagram is considered effective as a promotional medium, because people tend to be more interested in visual language than textual language. The Lawu Park carries out promotions via the Instagram social media account with the account name @the_lawupark. The purpose of this research is to find out what The Lawu Park does in promoting via Instagram social media and how much influence these promotions have on interest in visiting The Lawu Park. This research uses a descriptive type approach. Data collection was carried out through observation, interviews, questionnaires and document study. Then the data is generated through an interactive analysis process. The research results show that the promotion carried out by The Lawu Park is uploading images with certain criteria determined by management using experts in taking images, holding activities that support the promotion and always uploading images. Promotion via this Instagram account can influence followers' interest in visiting The Lawu Park. Keywords: Promotion, Instagram, Interest in Visiting